Enantioselective and Synergistic Herbicidal Activities of Common Amino Acids Against Amaranthus tricolor and Echinochloa crus-galli - Nawasit Chotsaeng; Chamroon Laosinwattana; Patchanee Charoenying (My University, 2021)
Amino acids have a wide range of biological activities, which usually rely on the stereoisomer presented. In this study, glycine and 21 common α-amino acids were investigated for their herbicidal property against Chinese amaranth (Amaranthus tricolor L.) and barnyard grass (Echinochloa crus-galli (L.) Beauv.). Both d- and l-isomers, as well as a racemic mixture, were tested and found that most compounds barely inhibited germination but moderately suppressed seedling growth. Various ratios of d:l-mixture were studied and synergy between enantiomers was found. For Chinese amaranth, the most toxic d:l-mixtures were at 3:7 (for glutamine), 8:2 (for methionine), and 5:5 (for tryptophan). For barnyard grass, rac-glutamine was more toxic than the pure forms; however, d-tryptophan exhibited greater activity than racemate and l-isomer, indicating the sign of enantioselective toxicity. The mode of action was unclear, but d-tryptophan caused bleaching of leaves, indicating pigment synthesis of the grass was inhibited. The results highlighted the enantioselective and synergistic toxicity of some amino acids, which relied upon plant species, chemical structures, and concentrations. Overall, our finding clarifies the effect of stereoisomers, and provides a chemical clue of amino acid herbicides, which may be useful in the development of herbicides from natural substances.
Keywords: Allelopathy and phytotoxic interactions